THE EFFECT OF THE ESNE (EDUCATION STRUCTURED NUTRITION AND ELECTROLYTE) METHOD ON IDWG CHANGES IN CHRONIC KIDNEY FAILURE PATIENTS - lutfi wahyuni; ika ainur rofiah; mochammad achwandi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
ABSTRACT Chronic kidney disease is a condition when kidney function begins to decline gradually. The condition of the decline in kidney function occurs due to many factors, one of which is because the kidney damage that has occurred intensely for many years. Patients with chronic renal failure need a management or hemodialysis therapy, which is the cleansing process of blood from waste substances, through a screening process outside the body using an artificial kidney in the form of a dialysis machine. Hemodialysis therapy is needed in the management of patients with chronic renal failure who cannot be treated again (terminal). The success of hemodialysis is based on various elements, one of which is compliance with fluid restrictions. Limitation of fluid intake in patients with chronic renal failure is very important. The provision of structured education can be given to patients with chronic kidney failure who are undergoing hemodialysis therapy. Education structured nutrition and electrolyte (ESNE) is a structured health education on nutrition and electrolyte management for chronic renal failure patients undergoing hemodialysis. ESNE is done to improve patients' understanding of diet and electrolyte compliance to prevent an increase in IDWG and to improve patient compliance with fluid restrictions. The stages of service activities that have been carried out are to explain fluid requirements and fluid restriction in patients with chronic renal failure using the Education structured nutrition and electrolyte (ESNE) method, the next recourse is an evaluation after continuous or ESNE administration of respondents given treatment and respondents who were not treated. Keywords: Diet, Chronic Kidney Disease, Hemodialysis